Impact Des Structures Fiscales Sur La Croissance Economique Au Congo-Brazzaville - Moussavou, Ferdinand (European Scientific Journal, ESJ, 2017)
This article proposes to make from Congolese data an empirical evaluation of the impact of tax structures on economic growth. It is based on the effects of state transfers to businesses and on the distinction between personal income taxes, corporate taxes and taxes on goods and services. The results obtained from Dickey and Fuller’s model show that, in the long term, personal income taxes, taxes on goods and services, total state revenues, state transfers to enterprises and gross fixed capital formation affect economic growth. In the short term, corporate taxes, revenues and transfers from the state to companies exert an influence on this growth. On the other hand, long-term and short-term results show that government revenues and transfers affect economic growth. These results made it possible to identify the limits of the economic policies implemented in Congo-Brazzaville.